PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT MANDIRI EXPRESS FORWADER TANGERANG SELATAN - Ghanafi Sandinata; Wahadi Siamto (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of Compensation and Work Motivation on Employee Performance at PT Mandiri Express Forwarder BSD City South Tangerang both partially and simultaneously. The method used is quantitative method. The sampling technique used was random sampling with a sample of 56 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of this study Hypothesis test obtained t count > t table (3.001 > 1,670). with a significance value of 0.000> 0.5, so with this H0 is rejected and H1 is accepted, meaning that there is a significant influence between Compensation (X1) on Employee Performance (Y) at PT Mandiri Express Forwarder. Hypothesis testing obtained t count > t table (4.601 > 1,670) with a significance value of 0.000> 0.5, so with this H0 is rejected and H2  is accepted, meaning that there is a significant influence between Work Motivation (X2) on Employee Performance (Y) at PT Mandiri Express Forwarder. Compensation and Motivation have a significant effect on Employee Performance with the hypothesis test value obtained f count > f table (32.119 > 3.150) with a significance value of 0.000> 0.5, thus H0 is rejected and H1 is accepted meaning that there is a significant influence between Compensation (X1) and Work Motivation (X2) on Employee Performance (Y) at PT Mandiri Express Forwarder.